-33=-2(r+6)

Simple and best practice solution for -33=-2(r+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -33=-2(r+6) equation:


Simplifying
-33 = -2(r + 6)

Reorder the terms:
-33 = -2(6 + r)
-33 = (6 * -2 + r * -2)
-33 = (-12 + -2r)

Solving
-33 = -12 + -2r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '2r' to each side of the equation.
-33 + 2r = -12 + -2r + 2r

Combine like terms: -2r + 2r = 0
-33 + 2r = -12 + 0
-33 + 2r = -12

Add '33' to each side of the equation.
-33 + 33 + 2r = -12 + 33

Combine like terms: -33 + 33 = 0
0 + 2r = -12 + 33
2r = -12 + 33

Combine like terms: -12 + 33 = 21
2r = 21

Divide each side by '2'.
r = 10.5

Simplifying
r = 10.5

See similar equations:

| 3(x+3)=144 | | 7y-21-5=-5y+8 | | 1.5(4-x)=1.3(3-x) | | -5(x+1)+4(2x-5)=2(x+2)-8 | | 1.8y^2+144y-1800=0 | | -5(x+1)+4(2x-5)=3(x-4)+10 | | 4.99+18x+6.75x=144.99 | | x+bx+cx= | | 9x+3+2x-9y-8= | | x(x-2)=-8x | | 3(x+20)=155 | | 11=60-16t^2 | | 1.74y-6=0.09 | | 4x+16y=16 | | 5(5x-4)+4=-15 | | 66=12j | | 12a-20b+4= | | (5x^2+2x-6)+(2x^2+2x+15)-(7x^2-14)= | | x+54=5x | | 50-2*[14-18]-7= | | 0=x^3+6x^2-2x-4 | | x(x-6)=6x | | n+x+p=168 | | 0=6x^2+5x-6 | | -4.1(y-1.4)=-6.8 | | y*5=0 | | 5-4(3x+1)=1+4(2x+20) | | 50-2x[14-18]-7= | | 7-21xa=0 | | 0=20x^2+9x-20 | | -2(y+5)=-31 | | 4z+2z=5z-9 |

Equations solver categories